Декоративні сорти Louiseania triloba (Lindl.) Pachom. та її гібриди в умовах південного сходу України - Mezhenskyj, V.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
Results of introduction investigations both 9 cultivars of Louiseania triloba (Lindl.) Pachom. and 6 cultivars of Louiseania Carr. × Prunus L. hybrids under the conditions of the South-East of Ukraine have been presented. The new combination ×Prunoseania arnoldiana (Rehder) Mezh. comb. nov. for the hybrids of Louiseania triloba × Prunus cerasifera Ehrh. is proposed.